USE OF THE OTRS SYSTEM TO MANAGE INCIDENTS AND RAISE THE LEVEL OF SERVICES OFFERED BY COMPANIES - Cardoso Dos Santos Silva, Tainá; Del Vechio, Gustavo Henrique (Revista Interface Tecnológica, 2020)
The more companies invest in the interaction and automation of processes, the more they can increase the quality of their services and attendance to the public. That way, this study seeks to analyze the open source system called OTRS (Open-source Ticket Request System) and its resources for incident management and problem solving in the scope of businesses. After describing the essential tools available, the study makes a comparison between a traditional service flow and what are the advantages obtained by adopting OTRS for this process. What can be seen from this study is that OTRS offers many advantages for handling incidents, from better control and communication with customers to a more dynamic flow between different departments, in order to solve problems more quickly and efficiently. It is, therefore, a very interesting choice for companies that wish to raise the level of their services.